Sea urchin sperm chemotaxis: individual effects and fertilization success - Hussain, Yasmeen Hajer (My University, 2017)
Egg chemoattraction of conspecific sperm mediates fertilization, a critical juncture in reproduction, especially in broadcast-spawning organisms like sea urchins. In the century that sea urchin sperm chemotaxis was studied before I started my work, many discoveries were made about the variety of peptide attractants that sea urchin eggs release into the ocean environment and the molecular mechanisms of the sperm chemotactic response. However, many questions were left unanswered. Particularly, previous work has focused on the patterns that persist across populations - it is well-known that chemotaxis generally changes sperm behavior and increases recruitment to eggs. In contrast, the differences between female and male sea urchin individuals and how those differences affect the dynamics of chemoattraction and chemotaxis has not been well-studied. In this dissertation, I studied not only average behavior but also individual differences. I (i) investigated whether differences in sperm chemotactic ability between individual males translated to differences in fertilization success, (ii) measured the chemoattractant release from individual females in the framework of their ability to attract sperm, and (iii) studied the behavior and physiology of sperm in specific chemoattractant gradients to understand their threshold of recruitment and fertilization-relevant response. I used an enzyme to digest chemoattractant and measured the resulting difference in the percent of eggs fertilized, then used novel chemotaxis assays in microfluidic channels to compare individual male chemotactic performance to fertilization success. Through this study, I found that chemotaxis can explain differences in individual male fertilization success. I then used high-performance liquid chromatography to determine the amount of chemoattractant released by eggs of individual females, computational models to investigate the resulting gradients, and microfluidic chemotaxis assays to assess how variable gradients affect sperm behavior. Through this work, I found that individual females vary significantly in their attractant release, which can in turn significantly affect sperm’s ability to detect their chemoattractant gradients. Lastly, I used microfluidic chemotaxis assays coupled with calcium imaging tools to record concurrent sperm behavioral and physiologic responses to gradients of chemoattractant and applied data analytics methodologies to determine the amount of attractant needed to recruit sperm, and found a surprising amount of variation in individual sperm behavior. In summary, my dissertation is an investigation of sperm chemotaxis in the frame of the individual: how individual male fertilization success correlates with their sperm chemotactic ability, how differences between females in egg chemoattractant release change their surrounding chemoattractant gradients, and how variable chemoattractant gradients affect the behavior and physiology of aggregate and individual sperm.
Thesis (Ph.D.)--University of Washington, 2016-12
Keywords: Chemoattractant; Chemotaxis; Fertilization; Microfluidics; Sea urchin; Sperm; Biology; biology